Automatic particle detection and sorting in an electrokinetic microfluidic chip. Issue 5 (30th January 2013) - Song, Yongxin; Peng, Ran; Wang, Junsheng; Pan, Xinxiang; Sun, Yeqing; Li, Dongqing; Gaš, Bohuslav
<x xml:space="preserve">Abstract</x> This paper reports a lab‐on‐a‐chip device that can automatically detect and sort particles based on their size differences with a high resolution. The PDMS‐glass microfluidic chip is made by soft‐lithography technique. A differential resistive pulse sensor is employed to electrically detect the sizes of the particles in EOF generated by applying DC voltages across channels. The detected resistive pulse sensor signals, whose amplitudes are proportional to particles' sizes, will automatically trigger the sorting process that is controlled by applying a voltage pulse (36 V) whenever a target particle is detected. This method was applied to automatically detect and sort polystyrene particles and microalgae in aqueous solutions. Sorting 5 μm polymer particle from a mixture of 4‐ and 5‐μm polystyrene particles in aqueous solution, i.e. 1 μm sorting resolution, was demonstrated. The device described in this paper is simple, automatic, and label‐free with high sorting resolution. It has wide applications in sample pretreatment and target particles detection.